Board Game-Aided Teaching Approach: Effects on Students’ Conceptual Understanding in Chemistry - Sarosong, Raihana Batua; Latip, Haniyyah Inoray G. (Education, Science, and Technology International Conference, 2025)
Many students find Chemistry as one of the difficult subjects in secondary level as it is loaded with concepts that require not only understanding but also critical thinking and problem-solving skills. For this reason, the study aimed to investigate the effects of integrating board games in teaching Chemistry course. The research sample comprised of twenty-six (26) pairs of students from two intact classes of Grade 7 of Datu Mamintal Adiong Sr. Memorial National High School. They were matched according to the average of their First Quarter and Second Quarter Grades in Science during the school year 2023 to 2024. The students in the control group were exposed to conventional approach while the experimental group of students was exposed to board game-aided approach. The study utilized quasi-experiment with pretest-posttest control group design. Results revealed that experimental group of students’ level of conceptual understanding after the intervention showed progress (7.7% satisfactory, 76.9 % very satisfactory and 15.4 % outstanding, respectively). Additionally, it was found that there was no significant difference between the Conceptual Understanding Test mean scores of experimental and control groups before and after the intervention. Also, the findings showed that there was no significant difference between the control and experimental groups of students’ conceptual understating test mean gain score after the intervention. Thus, this study suggests that utilizing board games as an aid in teaching Chemistry concepts could still be helpful and applied since it does not bear negative outcomes to students’ conceptual understanding. In line with these, the researcher encourages future researchers to conduct comprehensive study how can these board games be applied more productively.